International and Domestic Discourses of Chins’a Special Economic Zones: An Instrument for New Projects - Costa, C. M.; Yichao, L. (Handbook of Research on Special Economic Zones as Regional Development Enablers, 2022)
Although China's Special Economic Zones (SEZs) have already been widely known, they are under-studied, and the existing literature is missing certain topics such as the study of official discourses on these SEZs. What this study attempts to address are these questions: Does the Chinese political discourse on SEZ development change in both the domestic and international contexts? How does the Chinese discourse adapt to the domestic and international audiences and adjust to their conjuncture? The authors search and analyze official five-year plans for discrepancies between discourses and interpretations from ministry to ministry, and between the Chinese and English versions of the official discourse. The aim is to introduce discourse analysis to this topic, contributing to the discussion a broader description and analysis of SEZ dynamics, as well as an overview of their adjustments in accordance with the ever-evolving Chinese political and economic projects.